2011
DOI: 10.1142/s0578563411002446
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Multiply Composite Artificial Bars for Bragg Scattering of Water Waves

Abstract: The Bragg scattering of water waves by multiply composite artificial bars was investigated both theoretically and experimentally. Miles' theory is first employed to derive general formulae to calculate Bragg reflection coefficients for multiply composite artificial bars with different shapes, spacings, bar heights, bar footprint, and the number of bars. The theory provides explicit expressions in estimating Bragg reflections over multiply composite bars in practical engineering applications. The undulating osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Notably, both the numerical and theoretical predictions of Bragg scattering neglect the role of the viscosity; most studies focus on the wave profile transformation of waves propagating over bottom undulations (e.g., Dalrymple and Kirby, 1986;Kirby and Anton, 1990;Hsu et al, 2003;Hsu et al, 2007;Tsai et al, 2011). The level of viscosity, however, can be important and in some situations the numerical results gathered when neglecting its influence fail to describe the real flow interaction process.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, both the numerical and theoretical predictions of Bragg scattering neglect the role of the viscosity; most studies focus on the wave profile transformation of waves propagating over bottom undulations (e.g., Dalrymple and Kirby, 1986;Kirby and Anton, 1990;Hsu et al, 2003;Hsu et al, 2007;Tsai et al, 2011). The level of viscosity, however, can be important and in some situations the numerical results gathered when neglecting its influence fail to describe the real flow interaction process.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu et al [30] numerically investigated the Bragg scattering of multiply composite artificial bars by varying the relative bar height and the number of bars with different intervals, and showed that the bandwidth of high-performance region was increased. Tsai et al [31] investigated theoretically and experimentally the Bragg scattering of water waves by multiple composite artificial bars with different shapes, spacings, bar heights, bar footprint, and the number of bars, and the increased bandwidth was observed. Recently, in the respect of free surface breakwater, Ding et al [32] numerically studied the interaction of water waves with multiple composite flexible membranes by changing the relative group spacing, the end condition, the number, the tension, the draft and the protrusion of the membranes, and found that the bandwidth of Bragg reflection was increased compared to the multiple uniform-spacing flexible membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu et al (2007) used a second-order fully non-linear Boussinesq type model to explore Bragg reflection of irregular waves. Tsai, Kuo, Lan, Hsu, and Chen (2011) investigated the Bragg scattering of multiply composite artificial bars and validated their results by using the EEMSE model (Hsu, Tsai, & Huang, 2003). However, linear theoretical and numerical predictions are limited to the potential assumptions used.…”
Section: Introductionmentioning
confidence: 99%